2019
DOI: 10.3390/ma12244147
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication, Corrosion, and Mechanical Properties of Magnetron Sputtered Cu–Zr–Al Metallic Glass Thin Film

Abstract: The appearance of thin film metallic glasses (TFMGs) is gaining increasing interest because of their unique mechanical and anticorrosion properties and potential engineering applications. In this study, Cu-Zr-Al ternary thin film metallic glasses were fabricated by using DC magnetron sputtering equipment with various target powers. The evolution of the structure was systematically investigated by grazing incidence X-ray diffractometer, scanning electron microscopy, and transmission electron microscopy. The dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…For Co(OH)Se, no obvious diffraction peak was detected due to the formation of a reduced crystalline structure owing to the partial substitution of the hydroxyl group with the selenyl group having a larger ionic size 8,9 . The high‐resolution TEM (HRTEM) image (Figure 1C) indicating short‐range ordered (1‐3 nm) domains demonstrated that Co(OH)Se has a low degree of crystallinity; the corresponding selected area electron diffraction (SAED) pattern consisting of several diffuse rings is given in Figure 1D 25,26 . The XRD and TEM results were consistent with the results from previous reports suggesting that short‐range atomic arrangements can exhibit disordered features 27 .…”
Section: Resultsmentioning
confidence: 58%
“…For Co(OH)Se, no obvious diffraction peak was detected due to the formation of a reduced crystalline structure owing to the partial substitution of the hydroxyl group with the selenyl group having a larger ionic size 8,9 . The high‐resolution TEM (HRTEM) image (Figure 1C) indicating short‐range ordered (1‐3 nm) domains demonstrated that Co(OH)Se has a low degree of crystallinity; the corresponding selected area electron diffraction (SAED) pattern consisting of several diffuse rings is given in Figure 1D 25,26 . The XRD and TEM results were consistent with the results from previous reports suggesting that short‐range atomic arrangements can exhibit disordered features 27 .…”
Section: Resultsmentioning
confidence: 58%
“…The negative influence of FeNi 3 on the corrosion resistance may be observed for the sample treated at 400 C, where the anodic branch of the polarization curve is shifted to a higher current density. [13] Although the study uses untreated steel for comparison, the samples have entirely different surfaces. In the process of forming the layer by CCPD, the polished substrates have low surface roughness.…”
Section: Discussionmentioning
confidence: 99%
“…The negative influence of FeNi 3 on the corrosion resistance may be observed for the sample treated at 400 °C, where the anodic branch of the polarization curve is shifted to a higher current density. [ 13 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations